1994
DOI: 10.1681/asn.v52138
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of neutrophils with epithelial cells

Abstract: Active inflammatory processes in organs lined by columnar epithelial cells are often characterized by abundant neutrophil migration. To reach an epithelial surface, neutrophils must leave the vasculature and cross the interstitium where signals may be generated that influence migration and/or epithelial function. Subsequently neutrophils migrate across epithelial linings by impaling intercellular junctions between epithelial cells and, in doing so, diminish the ability of epithelial linings to serve as a barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…32 Specifically, aberrant control of these infiltrating neutrophils can result in tissue damage in the colon caused by abundant reactive oxygen species. [33][34][35] However, recent studies demonstrated that neutrophils IL-22 remains one of the most intriguing cytokines due to its ability to elicit completely different responses based on the microenvironment. In the context of the intestines, the presence of IL-22 appears to be beneficial under most circumstances including IBD, graft-versushost disease, and many types of bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Specifically, aberrant control of these infiltrating neutrophils can result in tissue damage in the colon caused by abundant reactive oxygen species. [33][34][35] However, recent studies demonstrated that neutrophils IL-22 remains one of the most intriguing cytokines due to its ability to elicit completely different responses based on the microenvironment. In the context of the intestines, the presence of IL-22 appears to be beneficial under most circumstances including IBD, graft-versushost disease, and many types of bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of colitis, the innate immune response in the colon includes recruited macrophages and neutrophils, which appear to have both proinflammatory and anti‐inflammatory roles in colitis 32 . Specifically, aberrant control of these infiltrating neutrophils can result in tissue damage in the colon caused by abundant reactive oxygen species 33–35 . However, recent studies demonstrated that neutrophils can play a protective role in the host response in acute models of colitis by producing IL‐22 36,10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation